2006
DOI: 10.1080/01402380500389364
|View full text |Cite
|
Sign up to set email alerts
|

Governing at the frontier of the European commission: The case of seconded national officials

Abstract: Studies of executive institutions have largely dealt separately with national and international executive institutions (IEIs). This study unpacks and repacks four conflicting decision-making dynamics that unfolds at the frontier of IEIs -that is, at the institutional rim where national and international executive institutions meet, interact and collide. The empirical laboratory utilised is seconded national experts in the European Commission. The survey and interview data presented demonstrates that the decisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(43 citation statements)
references
References 32 publications
(28 reference statements)
2
40
0
1
Order By: Relevance
“…A survey study of 71 national experts showed that they overwhelmingly identify with their respective DGs/Units or an independent expert role rather than with their respective national governments. Accordingly, in their daily work, they pay most attention to signals from their directors in the Commission and little attention to signals from their home governments (Trondal 2006).…”
Section: Executive Centre Formation At the European Levelmentioning
confidence: 99%
“…A survey study of 71 national experts showed that they overwhelmingly identify with their respective DGs/Units or an independent expert role rather than with their respective national governments. Accordingly, in their daily work, they pay most attention to signals from their directors in the Commission and little attention to signals from their home governments (Trondal 2006).…”
Section: Executive Centre Formation At the European Levelmentioning
confidence: 99%
“…The growing significance of SNEs within the Commission has only recently received attention in the literature, namely through the work of Jarle Trondal (2004Trondal ( , 2006aTrondal ( , 2006b). Trondal was the first scholar to collect data on SNEs.…”
Section: Getting Inside the Insiders: Methodology And Datamentioning
confidence: 99%
“…To use the a popular phrase from a US senator, NATO had to go "out-of-area or out of business" (Lugar 1993 (Kleine 2013), while lower positions may be subject to geographical balance. Third, contract policy also affects control with staff on permanent contracts having more autonomy than 'temporaries' or 'secondees' (Trondal 2006;Trondal, van den Berg and Suvarierol 2008). Finally, large member states may have privileged access allowing them to exert excessive informal influence (Stone 2011).…”
Section: Functionalism Multiple Principals and Institutional Reformmentioning
confidence: 99%